Theme-oriented discourse analysis of medical encounters - Roberts, Celia; Sarangi, Srikant (Medical education, 2005)
Approach  Theme‐oriented discourse analysis looks at how language constructs professional practice. Recordings of naturally occurring interactions are transcribed and combined with ethnographic knowledge. Analytic themes drawn primarily from sociology and linguistics shed light on how meaning is negotiated in interaction. Detailed features of talk, such as intonation and choice of vocabulary, trigger inferences about what is going on and being talked about. These affect how interactants judge each other and decisions are made. Interactions also have larger rhetorical patterns used by both patients and doctors to persuade each other. Examples  Two settings are used to illustrate this approach: genetic counselling and primary care consultations in multilingual areas. In genetic counselling, interactions are organised around the tension between the risks of knowing and the risks of occurrence. This can lead to a ‘rhetorical duel’ between health professionals and patients and their families. In intercultural primary care settings, talk itself may be the problem when interpretive processes cannot be taken for granted. Even widely held models of good practice can lead to misunderstandings under these conditions. Conclusion  Through discourse analysis, the talk under scrutiny can be slowed down to show the interpretive processes and overall patterns of an activity. Discourse analysts and health professionals, working together, can look at problems in new ways and develop interventions and tools for a better understanding of communication in medical life.